Peran Guru dalam Menstimulasi Kemampuan Menggambar pada Anak Usia Dini di Raudhatul Athfal Kuningan Jawa Barat - laila, Nur; Ulfah, Maulidya; Yani, Ahmad (Journal of Studies in Early Childhood Education (J-SECE), 2018)
Drawing Activities is one form of learning that serve as aspects of early childhood development. This activity is often applied in RA Qurrata Ayun Kuningan. Drawing activities can run smoothly with stimulus provided by educators, so it is important for teachers to have a standard as a teacher who has creativity and has the ability to compete as a professional early childhood educator. This research is motivated by teachers who have difficulty in conditioning class, problems in this activity often occur because of lack of spirit and confidence of children to the work of drawing. This study aims to increase creativity in the development of childrens talent interest in childrens fine motor The type of research used is qualitative descriptive. Subjects in this study were children in RA Qurrata Ayun Kuningan. The means used to collect this using Observation techniques, interviews and documentation. The results of the research have shown that the role of teachers in stimulating childrens drawing ability, they have role as learning seminar, manager, facilitator, manager, demonstrator, mentor, motivator, evaluator, mediator. Evident from the results of the teachers assessment of the supervisor with a description of Good, the assessment is derived from the daily learning process of teacher which has been observed by the madrasah supervisor. From the results of the observed research, in the process of drawing activity in the children get the results well in the field of art competence. Although, among them there are some children who still find it difficult in drawing. But it can be concluded with the role of appropriate early childhood teachers will achieve the level of child development achievement, especially in the process of drawing activities to support the development of aspects of the development of art, motor and knowledge of what is seen and known that will be expressed through the art images in early childhood.   Keywords: teacher, stimulate, drawing and early childhood   Kegiatan Menggambar merupakan salah satu bentuk pembelajaran aspek perkembangan anak usia dini. Kegiatan ini diterapkan di RA Qurrata Aâyun Kuningan. Kegiatan ini dapat berjalan lancar dengan diberikannya stimulus oleh pendidik, untuk itu guru harus memiliki standar kreatif dan kemampuan kompetensi sebagai pendidik anak usia dini yang profesional. Penelitian ini dilatar belakangi oleh guru yang mengalami kesulitan dalam mengelola kelas dan kepercayaan diri anak terhadap hasil karya menggambar. Penelitian ini bertujuan untuk meningkatkan kreatifitas dalam pengembangan seni  dan motorik halus anak. Jenis penelitian adalah dekriptif kualitatif. Subjek adalah anak di RA Qurrata Aâyun Kuningan. Cara yang digunakan untuk mengumpulkan data ini menggunakan observasi, wawancara dan dokumentasi. Hasil penelitian menunjukan bahwa peran guru dalam menstimulasi kemampuan menggambar pada anak yaitu sebagai sember belajar, pengelola, fasilitator, pengelola, demonstrator, pembimbing, motivator, evaluator, mediator. Terbukti dari hasil penilaian guru dari pengawas dengan keterangan baik, penilaian tersebut diperoleh dari proses pembelajaran sehari-hari guru yang  telah diamati oleh pengawas madrasah. Proses kegiatan menggambar pada anak mendapatkan hasil dengan baik dalam bidang kompetensi seni. Dapat disimpulkan bahwa dengan adanya peran guru yang sesuai maka akan tercapainya tingkat capaian perkembangan anak khususnya dalam  proses kegiatan menggambar pada aspek perkembangan seni, motorik terhadap apa yang dilihat dan diketahui yang akan diekspresikan melalui seni gambar pada anak usia dini.     Kata Kunci: guru, stimulus, menggambar dan anak ssia dini